2013
DOI: 10.1248/bpb.b13-00538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inhibitory Duration of Grapefruit Juice on Organic Anion-Transporting Polypeptide and Cytochrome P450 3A4

Abstract: Recently, a new type of interaction has been reported in which fruit juices diminish oral drug bioavailability through inhibition of organic anion-transporting polypeptide (OATP). In this study, we aimed to clarify the duration of OATP inhibition by grapefruit juice (GFJ), and to compare it with the duration of GFJ-induced inhibition of cytochrome P450 (CYP) 3A4 activity. Seven healthy volunteers were enrolled in this open-label, single-sequence study. They were orally administered celiprolol (100 mg) and mida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…8 -12 Although the ingestion of grapefruit juice has been shown to reduce the activity of intestinal cytochrome P450 3A4 (CYP3A4) and produce potential drug-nutrient interactions (eg, increased bioavailability) of drugs that are CYP3A4 substrates (eg, cyclosporine, tacrolimus, atorvastatin, felodipine, fexofenadine, specific antiretroviral agents), recent evidence suggests that grapefruit juice can also inhibit organic acid transporter activity. 9 In addition to grapefruit juice, flavonoids present in oranges and apples have also been shown to reduce the activity of the organic acid transporter OATP2B1. 8 Although the grapefruit juice-CYP3A4 substrate interaction and the potential for producing significant nutrient-drug interactions is the most well characterized, it should be noted that, in addition to inhibiting CYP3A4 activity, cranberry, pomegranate, and blueberry juice can inhibit the activity of CYP2C9, 10,12 a cytochrome P450 isoform that catalyzes the biotransformation of therapeutic drugs such as ibuprofen, flurbiprofen, warfarin, phenytoin, fluvastatin, and amitriptyline.…”
Section: Pharmacologic Considerations Associated With Fruit Juice Ingmentioning
confidence: 99%
See 1 more Smart Citation
“…8 -12 Although the ingestion of grapefruit juice has been shown to reduce the activity of intestinal cytochrome P450 3A4 (CYP3A4) and produce potential drug-nutrient interactions (eg, increased bioavailability) of drugs that are CYP3A4 substrates (eg, cyclosporine, tacrolimus, atorvastatin, felodipine, fexofenadine, specific antiretroviral agents), recent evidence suggests that grapefruit juice can also inhibit organic acid transporter activity. 9 In addition to grapefruit juice, flavonoids present in oranges and apples have also been shown to reduce the activity of the organic acid transporter OATP2B1. 8 Although the grapefruit juice-CYP3A4 substrate interaction and the potential for producing significant nutrient-drug interactions is the most well characterized, it should be noted that, in addition to inhibiting CYP3A4 activity, cranberry, pomegranate, and blueberry juice can inhibit the activity of CYP2C9, 10,12 a cytochrome P450 isoform that catalyzes the biotransformation of therapeutic drugs such as ibuprofen, flurbiprofen, warfarin, phenytoin, fluvastatin, and amitriptyline.…”
Section: Pharmacologic Considerations Associated With Fruit Juice Ingmentioning
confidence: 99%
“…10 In evaluating the potential juice-drug interactions, the coadministration of fruit juice and a drug for which metabolism or transport could be affected by a flavonoid should not be considered immediately as a contraindication for treatment. The amount and type of juice being ingested, 9 specific information characterizing a given interaction, and whether the drug(s) being taken has a low (eg, antiretrovirals, calcineurin inhibitors, calcium channel blockers, warfarin) or high therapeutic index must be considered in the evaluation of a potential interaction. Consultation between the physician and pharmacist can be beneficial in considering the potential clinical significance of a juice-drug interaction.…”
Section: Pharmacologic Considerations Associated With Fruit Juice Ingmentioning
confidence: 99%
“…28 The grapefruit is a textbook example of a CYP3A4 inhibitor, and the grapefruit juice-mediated CYP3A4 reaction plays an important role in organic anion-transporting polypeptide (OATP) metabolism. 29 The Lineweaver-Burk plots of inhibitory kinetic data in this paper showed that dioscin is a potent and reversible competitive inhibitor of CYP3A4, with K i ¼ 15.5 mM (Fig. 4C).…”
Section: Resultsmentioning
confidence: 57%
“…Regarding duration of activity of GFJ on OATP, Kim and colleagues reported that consumption of GFJ concomitantly or 2 hours before fexofenadine administration was associated with reduced oral fexofenadine plasma concentrations, whereas fexofenadine exposure was not affected when GFJ was taken 4 hours before drug administration . Recently, Tanaka et al compared the inhibitory duration of GFJ on celiprolol (an OATP substrate) and midazolam (a CYP3A substrate) in healthy volunteers, and their results also indicated that GFJ inhibition on OATP appears to dissipate over a shorter period than has been observed with CYP3A inhibition . In addition to the inhibitory duration of GFJ on OATP, the effect of GFJ volume on OATP inhibition was also evaluated .…”
Section: Oatp‐mediated Beverage–drug Interactionmentioning
confidence: 99%